Interrogating the New Economy: Restructuring Work in the 21st Century - Russell, Bob (Relations industrielles / Industrial Relations, 2010)
Interrogating the New Economy: Restructuring Work in the 21st Century, edited by Norene J. Pupa and Mark P. Thomas, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Employment; Global economy; Labor Unions; Labor force; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Transition economies; Unionization